Gaining Insight into Operative Performance: Analysis of an Automated 360-Degree Feedback Tool Among Perioperative Staff - Stefanie J. Soelling, MD, MPH; Robert D. Sinyard, MD; Lauren Spigel, MPH; Max Riley, MD; Paul Gregory, PhD; Nick Perdomo, MS; Yves Sonnay, MScPH; Steven Yule, PhD; Steven J. Fishman, MD; Douglas S. Smink, MD, MPH, FACS (Annals of Surgery Open)
Background:. Surgery has seen limited adoption of 360-degree feedback tools, and no current tools evaluate intraoperative performance from a technical, nontechnical, or teaching skill perspective. We sought to evaluate the overall findings and perceived value of a novel 360-degree feedback tool for surgeons from their operating room colleagues. Methods:. The ‘intraoperative 360’ (i360) combined 3 previously validated scales of surgeon performance. The electronic medical record at a single academic medical center was queried for perioperative staff involvement in recent cases for a cohort of surgeons. Staff with frequent surgeon case involvement were emailed a link to an anonymous i360 survey. Aggregated survey responses were provided to surgeons and surgical leadership. We performed semi-structured interviews with 10 surgeons and 5 surgical leaders. Combined inductive and deductive coding was used to determine their perceptions regarding the utility of and barriers to the i360. Results:. Over 2-years, a total of 960 surveys were completed for 88 surgeons. The composite rating of technical skills was 4.87/5 (SD: 0.36); nontechnical skills, 4.65/5 (SD: 0.55); and teaching skills, 2.92/3 (SD: 0.24). There was no difference in mean scores based on gender, age, or years of tenure. Six themes emerged from the interviews: initial reactions, utility, additional needs, other feedback mechanisms, reciprocal feedback, and logistical challenges. Conclusions:. A 360-degree feedback tool is feasible, and feedback is perceived as valuable and actionable for surgeons and surgeon leaders. The intraoperative focus provided surgeons with specific feedback on how to improve within the operating room to promote efficiency, teamwork, and patient safety.